Scientific research in the tourism, leisure and hospitality field: a bibliometric analysis. Issue 3 (2nd July 2020) - Merigó, José M.; Mulet-Forteza, Carles; Martorell, Onofre; Merigó-Lindahl, Carolina
ABSTRACT: This paper presents an overview of the most cited papers in all the journals indexed in the Web of Science in the tourism, leisure and hospitality fields through a bibliometric approach. The paper presents several lists with the most cited papers and the publication and citation structure of the last decades in the tourism, leisure and hospitality fields. It also analyzes how the main topics and keywords have changed in these areas in order to raise awareness of the topics and keywords that will predominate in the research in these fields over the next years.